2019
DOI: 10.1089/thy.2018.0664
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease and Hypercholesterolemia: Roles of Thyroid Hormones, Metabolites, and Agonists

Abstract: Background-Thyroid hormones (THs) exert a strong influence on mammalian lipid metabolism at the systemic and hepatic levels by virtue of their roles in regulating circulating lipoprotein, triglyceride (TAG), and cholesterol levels, as well as hepatic TAG storage and metabolism. These effects are mediated by intricate sensing and feedback systems that function at the physiological, metabolic, molecular, and transcriptional levels in the liver. Dysfunction in the pathways involved in lipid metabolism disrupts he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
149
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(155 citation statements)
references
References 170 publications
(214 reference statements)
1
149
0
5
Order By: Relevance
“…The thyroid hormone receptor β (THR β) is highly expressed in hepatocytes and is responsible for regulating the metabolic pathways in the liver that are frequently impaired in NAFLD and NASH. 13 Resmetirom (MGL-3196, Madrigal Pharmaceuticals Inc), a highly selective THR β agonist, has been developed to target dyslipidemia but has also been shown to reduce hepatic steatosis in fat-fed rats, improving insulin sen- and did not result in study withdrawal. 15 A phase 3 in patients with NASH and fibrosis is now recruiting (https ://clini caltr ials.gov/ct2/show/NCT03 900429).…”
Section: Resmetirom (Mgl-3196)mentioning
confidence: 99%
“…The thyroid hormone receptor β (THR β) is highly expressed in hepatocytes and is responsible for regulating the metabolic pathways in the liver that are frequently impaired in NAFLD and NASH. 13 Resmetirom (MGL-3196, Madrigal Pharmaceuticals Inc), a highly selective THR β agonist, has been developed to target dyslipidemia but has also been shown to reduce hepatic steatosis in fat-fed rats, improving insulin sen- and did not result in study withdrawal. 15 A phase 3 in patients with NASH and fibrosis is now recruiting (https ://clini caltr ials.gov/ct2/show/NCT03 900429).…”
Section: Resmetirom (Mgl-3196)mentioning
confidence: 99%
“…Thyroid hormones (THs), T 4 , and the more biologically active form, T 3 , stimulate fatty acid β-oxidation and oxidative phosphorylation in the liver. (2) Numerous studies have shown an inverse relationship between serum TH levels and NAFLD given that patients with hypothyroidism and subclinical hypothyroidism have increased risk for NAFLD and vice versa. (3) Transcriptomes of liver samples obtained from bariatric surgery patients also showed that the most prominent altered gene set was associated with TH action.…”
Section: Thyroid Hormones and Thyromimetics: A New Approach To Nonalcmentioning
confidence: 99%
“…(4) Additionally, T 3 and several thyromimetics decreased intrahepatic triglycerides in rodent models of hepatosteatosis. (2) Although TH increases the transcription of carnitine palmitoyl-transferase 1alpha (a carrier protein that promotes fatty acid uptake into mitochondria) and adipose triglyceride lipase (a lipase that converts triglycerides to fatty acids), hepatic autophagy of fat droplets and their conversion to free fatty acids within fused autolysosomes (lipophagy) appears to be crucial for TH-mediated β-oxidation of fatty acids. (5) Additionally, TH maintains mitochondria quality during this process by autophagy of mitochondria (mitophagy) and mitochondrial biogenesis.…”
Section: Thyroid Hormones and Thyromimetics: A New Approach To Nonalcmentioning
confidence: 99%
“…NAFLD is also associated with decreased sensitivity to thyroid hormones [116] and both NAFLD and HCC are associated with hypothyroidism in humans [117,118] . Furthermore, thyroid hormone treatment decreases hepatosteatosis and the progression of NAFLD in both rodents and humans [119] . Several new studies provide evidence for a potential role of androgen and the androgen receptor pathway in the development of NASH-related HCC and in the treatment of HCC [120] .…”
Section: Endocrine Pathwaysmentioning
confidence: 99%